2008
DOI: 10.1111/j.1600-0463.2008.01092.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical isolates of Staphylococcus aureus from the Arkhangelsk region, Russia: antimicrobial susceptibility, molecular epidemiology, and distribution of Panton‐Valentine leucocidin genes

Abstract: A total of 91 consecutive clinical isolates of Staphylococcus aureus were collected at the Regional Hospital of Arkhangelsk, Russia, from May to December 2004, and examined for antimicrobial susceptibility, methicillin resistance and presence of Panton-Valentine leucocidin (PVL) genes. Epidemiological typing was performed by pulsed-field gel electrophoresis (PFGE) and multilocus sequence typing (MLST). Methicillin-resistant S. aureus (MRSA) isolates were examined by staphylococcal cassette chromosome mec (SCCm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
19
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 39 publications
11
19
0
Order By: Relevance
“…37%, is similar to that reported in a study conducted in the Arkhangelsk region of Russia (26). However, other studies that used a methodology similar to that of our study reported much lower prevalence rates, ranging from 7 to 12% (13,21,29).…”
Section: Discussionsupporting
confidence: 90%
“…37%, is similar to that reported in a study conducted in the Arkhangelsk region of Russia (26). However, other studies that used a methodology similar to that of our study reported much lower prevalence rates, ranging from 7 to 12% (13,21,29).…”
Section: Discussionsupporting
confidence: 90%
“…Although eight clonal types (Table 1) were identified among the isolates, 63% (n=19) belonged to a single type: PFGE A, spa type t159, sequence type (ST) 121, agr type IV. The ST121 lineage was also the predominant lineage found in MSSA isolates through Europe and Russia [23][24][25] and an identical scenario has been reported among Asiatic children in both carriage and disease isolates, and frequently associated to PVL. Of major concern was the local emergence of methicillin resistance in ST121 isolates in these pediatric communities: one MRSA isolate, PVLnegative responsible for staphylococcal scalded skin syndrome in China and two MRSA, PVL-positive, SCCmec type V isolates responsible for osteomyelitis and soft tissue abscess in Cambodia [26,27].…”
supporting
confidence: 67%
“…SSTIs caused by luk-PV-positive MSSA CC121 strains have been reported from Saxony and Brandenburg in Germany as well as from hospitals in Russia, showing that this CC has a worldwide distribution (4,39,55,58). Similar strains also caused highly lethal community-acquired pneumonia and severe sepsis with progressive metastatic soft tissue infection (4,46), demonstrating the virulence potential of this lineage.…”
Section: Discussionmentioning
confidence: 94%